PERAN PENTING SELF-NANOEMULSIFYING DRUG DELIVERY SYSTEM (SNEDDS) DALAM MENINGKATKAN EFEKTIFITAS EKSTRAK HERBAL DALAM PENGOBATAN DI INDONESIA: REVIEW ARTIKEL - Prima Aulia Putra; Lutfi Chabib; Arba Pramundita; Hady Anshory (Jurnal Farmasi IKIFA, 2025)
Indonesia is a country dubbed as the world's herbal home, reaching 75% of natural ingredients found in Indonesia. However, most natural ingredients currently experience constraints in water solubility, resulting in suboptimal dissolution and decreased bioavailability. To overcome this problem, various techniques have been developed, salt formation, particle size reduction, solid dispersion, lipid-based formulations, and so on. One approach that is increasingly gaining attention in improving the solubility of lipophilic drugs is the self-nanoemulsifying drug delivery system (SNEDDS). SNEDDS is an isotropic mixture of oil, surfactants, and co-surfactants that forms oil-in-water (o/w) nanoemulsions with minimal stirring. This approach is becoming increasingly important in efforts to improve drug solubility and, therefore, increase the efficiency of lipophilic drug delivery. The application of the SNEDDS method to herbal medicine formulas will increase effectiveness and improve their bioavailability properties, thereby increasing efficiency in utilizing the potential of medicinal plants in Indonesia.